A high-strength cellulose acetate material and its preparation method and application
By using the formulation of aryl ether sulfone monomaleimide and epoxidized alkyl ester compositions, combined with the processing technology of ultrasonic twin screw extruder, the high level of cellulose diacetate processing is solved. The glass conversion temperature and low flowability problems achieve high mechanical strength and thermal stability of the material.
Patent Information
- Application Number
- CN202411011834.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-07-26
AI Technical Summary
During processing, due to the high glass conversion temperature, the melt processing temperature is close to the degradation temperature, the processing capacity is limited, and the heat resistance and flowability are poor.
The formulation of 65%-75% cellulose diacetate grafted arylethersulfone monomaleimide, 23%-33% epoxidized alkyl ester composition and 1%-2% antioxidant was adopted by Ultrasonic twin-screw extruder is processed to reduce the glass transition temperature and improve fluidity and mechanical strength.
It effectively reduces the glass transition temperature of cellulose diacetate, improves its fluidity and mechanical strength, avoids carbonization and degradation problems, and enhances the thermal stability and mechanical properties of the material.
Smart Images

Figure QLYQS_1 
Figure BDA0004964601810000031 
Figure BDA0004964601810000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cellulose acetate materials, and in particular to a high-strength cellulose acetate material and a preparation method and application thereof. Background Art
[0002] Cellulose acetate is the acetate ester of cellulose, a chemically modified natural polymer obtained by esterifying the hydroxyl groups in the cellulose molecule with acetate. Cellulose acetate is mainly divided into two categories: diacetate and triacetate. Its performance depends on the degree of acetylation, that is, the average number of hydroxyl groups of the glucose units of cellulose replaced by acetyl groups. Diacetate is formed by partial hydrolysis of cellulose acetate, and its degree of esterification is lower than that of triacetate. Therefore, its thermal performance is not as good as triacetate, but its dyeing performance is better than triacetate, and its moisture absorption rate is higher than that of triacetate. Triacetate is not hydrolyzed, and its degree of esterification is higher. Therefore, it has strong light and heat resistance, poor dyeing performance, and low moisture absorption rate (also known as regain).
[0003] When the degree of substitution of cellulose is less than 2.0, the molecular fluidity during melting will be reduced, the biodegradability will be poor, and the acetate fiber will carbonize at high temperature during melting. When cellulose diacetate is processed, due to the high glass transition temperature (Tg) of cellulose diacetate, its melt processing temperature even exceeds the degradation temperature (Td). Because the glass transition temperature (Tg) is close to the decomposition temperature, the temperature window for processing is very narrow, resulting in limited processing capacity. Cellulose diacetate decomposes before melt flow. Therefore, it is very important to reduce the glass transition temperature (Tg) of cellulose diacetate and improve the fluidity of cellulose diacetate. This material needs to be plasticized to improve its thermal and tensile properties. In addition, the molecular structure of cellulose diacetate contains a large number of highly polar hydroxyl groups, the hydrogen bonds between the molecular chains of cellulose diacetate are strong, the fluidity in the molten state is poor, and it is easy to carbonize and decompose under high temperature processing, and the heat resistance is poor. In order to improve the fluidity of cellulose diacetate in the molten state, a certain amount of plasticizer is often added during the processing of cellulose diacetate. In different applications, the amount of plasticizer added is usually between 15% and 35%. Commonly used plasticizers include: fatty acid esters, o-phenyl esters, citrate esters, etc., and the type and amount of plasticizers also have a certain effect on the heat resistance of cellulose diacetate. The heat resistance of the plasticizer determines its stability at high temperatures. Once the plasticizer decomposes at high temperatures, the heat resistance of cellulose diacetate will also deteriorate. The degradation of the plasticizer leads to the formation of pores on the surface of the mixture of plasticizer and cellulose diacetate, thereby accelerating the degradation process of cellulose diacetate. The reason is that a large number of cavities are generated on the surface of the mixture, providing a larger specific surface area for cellulose diacetate or providing an acidic environment for rapid degradation of cellulose diacetate, thereby promoting its degradation.
[0004] If the amount of plasticizer added is small, plasticization is not smooth, and carbides may be generated during the manufacturing process of cellulose diacetate slices or processability may not be smooth. If the amount of plasticizer added is large, the plasticizer softens the material, and excessive plasticizer significantly reduces the modulus and strength of the material. The strength of cellulose diacetate may be reduced due to the large amount of plasticizer. Excessive plasticizer will precipitate from the inside of the material and reduce the mechanical properties of the material. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, one of the objects of the present invention is to provide a high-strength cellulose acetate material, which is a liquid crystal polymer and has high mechanical strength.
[0006] A second object of the present invention is to provide a method for preparing a high-strength cellulose acetate material. The method has simple steps and can be used to industrially produce the high-strength cellulose acetate material.
[0007] A third object of the present invention is to provide an application of the high-strength cellulose acetate material.
[0008] One of the purposes of the present invention is achieved by the following technical solution:
[0009] A high-strength cellulose acetate material, the raw materials of which include, by mass percentage: 65%-75% of cellulose diacetate grafted aryl ether sulfone monomaleimide, 23%-33% of an epoxidized alkyl ester composition of a compound represented by formula 1, and 1%-2% of an antioxidant;
[0010] Formula 1
[0011]
[0012] In Formula 1, R1 is an alkyl group of 8 to 20 carbon atoms containing one to three epoxy groups, and R2 is an alkyl group of 4, 5, or 8 to 10 carbon atoms;
[0013] The cellulose diacetate grafted aryl ether sulfone monomaleimide is a liquid crystal polymer, wherein the aryl ether sulfone monomaleimide is a liquid crystal phase.
[0014] Furthermore, the raw materials, calculated by mass percentage, include: 70% of cellulose diacetate grafted aryl ether sulfone monomaleimide, 28% of the epoxidized alkyl ester composition of the compound represented by Formula 1, and 2% of an antioxidant.
[0015] Furthermore, the antioxidant is tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane or tris(2,4-di-tert-butylphenyl)phosphite.
[0016] Further, R2 in Formula 1 is selected from butyl, pentyl, 2-ethylhexyl, isononyl and 2-propylheptyl.
[0017] Furthermore, the preparation method of the cellulose diacetate grafted aryl ether sulfone monomaleimide comprises the following steps:
[0018] S1. Synthesis and purification of aromatic ether sulfone diamine: p-aminophenol, dichlorodiphenol, dimethyl sulfoxide, sodium hydroxide and toluene were added to a four-necked flask equipped with a stirrer, a water separator, a thermometer and a N2 tube, and the mixture was reacted at 120°C to 140°C for 5 hours. After the reaction, the toluene was evaporated, sodium hydroxide was added to make the mixture alkaline, the precipitate was separated, and the mixture was washed with water, alcohol and dried.
[0019] S2, cellulose diacetate grafted with aromatic ether sulfone diamine: adding the aromatic ether sulfone diamine to a cellulose diacetate solution dissolved in cyclohexanone, reacting at 70° C. for 30 h, with an ultrasonic power of 1050 W, precipitating the reaction product in cold methanol, filtering, and washing with methanol to obtain the cellulose diacetate grafted with aromatic ether sulfone diamine;
[0020] S3. Synthesis of cellulose diacetate grafted aryl ether sulfone monomaleimide (SEM):
[0021] In a three-necked flask equipped with a stirrer, a thermometer and a condenser, maleic anhydride is added and dissolved in dimethylformamide. The diacetate cellulose grafted with aromatic ether sulfone diamine (molar ratio 2.2:1) is added under stirring, cooled with cold water, reacted at 10°C to 25°C for 1 hour to obtain diacetate cellulose grafted with monomaleamic acid, and then p-toluenesulfonic acid and toluene are added, the temperature is slowly raised to 120°C, reacted for 4 hours, cooled to room temperature, poured into distilled water under stirring, the brown viscous substance is filtered out, the filtrate is rotary evaporated, dimethylformamide is added to dissolve it and precipitate it in water, filtered, washed with alcohol, and dried to obtain the diacetate cellulose grafted with aromatic ether sulfone monomaleimide.
[0022] Furthermore, the raw materials also include, by mass percentage: 1%-2% of a liquid crystal modifier.
[0023] Furthermore, the preparation method of the liquid crystal modifier comprises the following steps:
[0024] S1, 4-(2-propyleneoxy)benzaldehyde: 4-hydroxybenzaldehyde (61.1 g, 0.5 mol), anhydrous K2CO3 (82.8 g, 0.6 mol) and dimethylformamide solution (250 mL) were added to a 500 mL three-necked round-bottom flask equipped with a mechanical stirrer and a reflux condenser, respectively, and stirred for 15 min; allyl bromide (72.6 g, 0.6 mol) dissolved in 50 mL of dimethylformamide solution was slowly added to the three-necked round-bottom flask equipped with a mechanical stirrer and a reflux condenser, and the slow addition time was 30 min, and the mixture was refluxed under nitrogen for 24 h; then the obtained solution was poured into water, extracted three times with ether, and dried over anhydrous MgSO4. After the solvent was evaporated, a light yellow oil was obtained to obtain the 4-(2-propyleneoxy)benzaldehyde;
[0025] S1. Dienyloxyazoimide: The aromatic diamine and the 4-(2-propyleneoxy)benzaldehyde are mixed at a molar ratio of 1:2, the mixture is dissolved in a dimethylformamide solution, a few drops of acetic acid are added, and the mixture is heated at 80°C to react. After the reaction is completed, the mixture is cooled to room temperature, and the obtained solution is poured into water, the solid is filtered out, washed with ethanol, and vacuum dried to obtain the liquid crystal modifier.
[0026] The second object of the present invention is achieved by adopting the following technical solution:
[0027] A method for producing a high-strength cellulose acetate material comprises the following steps:
[0028] S1. Synthesis and purification of aromatic ether sulfone diamine: p-aminophenol, dichlorodiphenol, dimethyl sulfoxide, sodium hydroxide and toluene were added to a four-necked flask equipped with a stirrer, a water separator, a thermometer and a N2 tube, and the mixture was reacted at 120°C to 140°C for 5 hours. After the reaction, the toluene was evaporated, sodium hydroxide was added to make the mixture alkaline, and the precipitate was separated and finally washed with water, washed with alcohol, dried and set aside;
[0029] S2. At room temperature, cellulose diacetate and the epoxidized alkyl ester composition of the compound represented by Formula 1 are mixed in a high-speed mechanical stirrer for 2 minutes according to the formula amount, and then the mixture is dried in a vacuum oven at 70° C. to 90° C. for 20 to 30 hours to obtain a plasticized mixture;
[0030] S3, adding the plasticized mixture into an ultrasonic twin-screw extruder, then adding the antioxidant into the ultrasonic twin-screw extruder, adding the aromatic ether sulfone diamine during the melting process, reacting at a temperature of 70° C. for 30 hours and an ultrasonic power of 1050 W to obtain the cellulose diacetate grafted aromatic ether sulfone diamine;
[0031] S4. Add the maleic anhydride into the ultrasonic twin-screw extruder, add the cellulose diacetate grafted aromatic ether sulfone diamine (molar ratio 2.2:1) under stirring, react at 10°C to 25°C for 1 hour to obtain cellulose diacetate grafted monomaleamic acid, then add p-toluenesulfonic acid and toluene, slowly heat up to 120°C, react for 4 hours to obtain the cellulose diacetate grafted aromatic ether sulfone monomaleimide, and after extrusion, cool to room temperature to produce particles to obtain the cellulose acetate material with high strength.
[0032] Further, in step S2, the mixture is dried in a vacuum oven at 70° C. for 24 h.
[0033] A third object of the present invention is to provide an application of a cellulose acetate material with high strength.
[0034] Furthermore, the high-strength cellulose acetate material is used to manufacture eyeglass frames and high-end tool handles.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) The present invention provides a high-strength cellulose acetate material. The epoxidized alkyl ester composition of the compound represented by Formula 1 is used as a plasticizer, which has good thermal stability, can improve the plasticization efficiency of diacetyl cellulose, reduce the glass transition temperature (Tg) of diacetyl cellulose, and avoid carbonization of diacetyl cellulose during processing due to insufficient fluidity; the antioxidant can prevent diacetyl cellulose from decomposing due to high temperature during the melting and heating process of the twin-screw extruder, thereby improving the thermal stability of the high-strength cellulose acetate material; diacetyl cellulose grafted with aryl ether sulfone monomaleimide is a liquid crystal polymer, wherein the aryl ether sulfone monomaleimide is a liquid crystal phase, which can improve the mechanical strength of the high-strength cellulose acetate material; the amino group of the aryl ether sulfone diamine can react with the acetyl group of the pyranose ring of the diacetyl cellulose, thereby being grafted onto the diacetyl cellulose;
[0037] (2) The high-strength cellulose acetate material provided by the present invention also includes a liquid crystal modifier, which can increase the cross-linking degree of the liquid crystal polymer network and further increase the mechanical strength of the liquid crystal polymer. DETAILED DESCRIPTION
[0038] The present invention is further described below in conjunction with specific embodiments. It should be noted that, under the premise of no conflict, the embodiments or technical features described below can be arbitrarily combined to form a new embodiment.
[0039] Cellulose diacetate was purchased from Sichuan Pushi Cellulose Acetate Co., Ltd., Changning, China; the acetylation content was about 40%, and the average acetylation degree (DS) of cellulose diacetate was 2.41 as determined by 1H-NMR; the average particle size (d50) of the powder was 250 μm, and the specific gravity was 1.20-1.32 g·cm -3 ; The glass transition temperature is about 198°C, and the melting temperature is between 230-250°C; Cellulose diacetate is used after vacuum drying at 70°C for more than 72 hours;
[0040] p-Aminophenol, dichlorodiphenol, dimethyl sulfoxide, sodium hydroxide, toluene, cyclohexanone, maleic anhydride, toluenesulfonic acid, 4-hydroxybenzaldehyde, dimethylformamide, allyl bromide, and aromatic diamines were purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0041] The antioxidants tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane and tris(2,4-di-tert-butylphenyl)phosphite were purchased from Hubei Xinrunde Chemical Co., Ltd.;
[0042] Rheological solid analyzer II was purchased from Shenzhen Xinyichuang Technology Co., Ltd.
[0043] Example 1
[0044] This embodiment provides a high-strength cellulose acetate material, wherein the raw materials include, by mass percentage: 70% of cellulose diacetate grafted aryl ether sulfone monomaleimide, 28% of an epoxidized alkyl ester composition of a compound represented by Formula 1, and 2% of an antioxidant.
[0045] Formula 1
[0046]
[0047] Among them, the antioxidant can prevent the decomposition of cellulose diacetate caused by high temperature during the melting and heating process of the twin-screw extruder.
[0048] In this embodiment, the antioxidant is tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane, that is, antioxidant 1010.
[0049] In Formula 1, R1 is an isononyl group having 8 carbon atoms and containing an epoxy group; and R2 is selected from a butyl group.
[0050] In this embodiment, the preparation method of cellulose diacetate grafted aryl ether sulfone monomaleimide comprises the following steps:
[0051] S1. Synthesis and purification of aromatic ether sulfone diamine: p-aminophenol, dichlorodiphenol, dimethyl sulfoxide, sodium hydroxide and toluene were added to a four-necked flask equipped with a stirrer, a water separator, a thermometer and a N2 tube, and the mixture was reacted at 120°C to 140°C for 5 hours. After the reaction, the toluene was evaporated, sodium hydroxide was added to make the mixture alkaline, the precipitate was separated, and the mixture was washed with water, alcohol and dried.
[0052] S2, cellulose diacetate grafted with aromatic ether sulfone diamine: adding aromatic ether sulfone diamine to a cellulose diacetate solution dissolved in cyclohexanone, reacting at 70°C for 30 hours, with an ultrasonic power of 1050W, and precipitating the reaction product in cold methanol, filtering, and washing with methanol to obtain cellulose diacetate grafted with aromatic ether sulfone diamine;
[0053] S3. Synthesis of cellulose diacetate grafted aryl ether sulfone monomaleimide (SEM):
[0054] In a three-necked flask equipped with a stirrer, a thermometer and a condenser, add maleic anhydride and dissolve it in dimethylformamide. Add diacetate cellulose grafted with aromatic ether sulfone diamine (molar ratio 2.2:1) under stirring, cool with cold water, react at 10°C to 25°C for 1h to obtain diacetate cellulose grafted with monomaleamic acid, then add p-toluenesulfonic acid and toluene, slowly heat to 120°C, react for 4h, cool to room temperature, pour into distilled water under stirring, filter out the brown viscous substance, rotary evaporate the filtrate, add dimethylformamide to dissolve it and precipitate it in water, filter, wash with alcohol, and dry to obtain diacetate cellulose grafted with aromatic ether sulfone monomaleimide.
[0055] This embodiment provides a method for preparing a high-strength cellulose acetate material, comprising the following steps:
[0056] S1. Synthesis and purification of aromatic ether sulfone diamine: p-aminophenol, dichlorodiphenol, dimethyl sulfoxide, sodium hydroxide and toluene were added to a four-necked flask equipped with a stirrer, a water separator, a thermometer and a N2 tube, and the mixture was reacted at 120°C to 140°C for 5 hours. After the reaction, the toluene was evaporated, sodium hydroxide was added to make the mixture alkaline, and the precipitate was separated and finally washed with water, washed with alcohol, dried and set aside;
[0057] S2. Mixing cellulose diacetate and the epoxidized alkyl ester composition of the compound represented by Formula 1 in a high-speed mechanical stirrer for 2 minutes at room temperature, and then drying the mixture in a vacuum oven at 70° C. for 24 hours to obtain a plasticized mixture;
[0058] S3, adding the plasticized mixture into an ultrasonic twin-screw extruder, then adding an antioxidant into the ultrasonic twin-screw extruder, adding aromatic ether sulfone diamine during the melting process, and reacting at a temperature of 70° C. for 30 hours and an ultrasonic power of 1050 W to obtain cellulose diacetate grafted with aromatic ether sulfone diamine;
[0059] S4. Add maleic anhydride to an ultrasonic twin-screw extruder, add diacetate cellulose grafted with aromatic ether sulfone diamine (molar ratio 2.2:1) under stirring, react at 10°C to 25°C for 1 hour to obtain diacetate cellulose grafted with monomaleamic acid, then add p-toluenesulfonic acid and toluene, slowly heat up to 120°C, react for 4 hours to obtain diacetate cellulose grafted with aromatic ether sulfone monomaleimide, and after extrusion, cool to room temperature to produce particles to obtain a high-strength cellulose acetate material.
[0060] Example 2
[0061] This embodiment provides a high-strength cellulose acetate material, wherein the raw materials include, by mass percentage: 75% of cellulose diacetate grafted aryl ether sulfone monomaleimide, 24% of an epoxidized alkyl ester composition of a compound represented by Formula 1, and 1% of an antioxidant;
[0062] Formula 1
[0063]
[0064] Among them, the antioxidant can prevent the decomposition of cellulose diacetate caused by high temperature during the melting and heating process of the twin-screw extruder.
[0065] In this embodiment, the antioxidant is tris(2,4-di-tert-butylphenyl)phosphite, namely antioxidant 168.
[0066] In Formula 1, R1 is an alkyl group of 20 carbon atoms containing two epoxy groups; and R2 is selected from a pentyl group.
[0067] In this embodiment, the preparation method of cellulose diacetate grafted aryl ether sulfone monomaleimide comprises the following steps:
[0068] S1. Synthesis and purification of aromatic ether sulfone diamine: p-aminophenol, dichlorodiphenol, dimethyl sulfoxide, sodium hydroxide and toluene were added to a four-necked flask equipped with a stirrer, a water separator, a thermometer and a N2 tube, and the mixture was reacted at 120°C to 140°C for 5 hours. After the reaction, the toluene was evaporated, sodium hydroxide was added to make the mixture alkaline, the precipitate was separated, and the mixture was washed with water, alcohol and dried.
[0069] S2, cellulose diacetate grafted with aromatic ether sulfone diamine: adding aromatic ether sulfone diamine to a cellulose diacetate solution dissolved in cyclohexanone, reacting at 70°C for 30 hours, with an ultrasonic power of 1050W, and precipitating the reaction product in cold methanol, filtering, and washing with methanol to obtain cellulose diacetate grafted with aromatic ether sulfone diamine;
[0070] S3. Synthesis of cellulose diacetate grafted aryl ether sulfone monomaleimide (SEM):
[0071] In a three-necked flask equipped with a stirrer, a thermometer and a condenser, add maleic anhydride and dissolve it in dimethylformamide. Add diacetate cellulose grafted with aromatic ether sulfone diamine (molar ratio 2.2:1) under stirring, cool with cold water, react at 10°C to 25°C for 1h to obtain diacetate cellulose grafted with monomaleamic acid, then add p-toluenesulfonic acid and toluene, slowly heat to 120°C, react for 4h, cool to room temperature, pour into distilled water under stirring, filter out the brown viscous substance, rotary evaporate the filtrate, add dimethylformamide to dissolve it and precipitate it in water, filter, wash with alcohol, and dry to obtain diacetate cellulose grafted with aromatic ether sulfone monomaleimide.
[0072] This embodiment provides a method for preparing a high-strength cellulose acetate material, comprising the following steps:
[0073] S1. Synthesis and purification of aromatic ether sulfone diamine: p-aminophenol, dichlorodiphenol, dimethyl sulfoxide, sodium hydroxide and toluene were added to a four-necked flask equipped with a stirrer, a water separator, a thermometer and a N2 tube, and the mixture was reacted at 120°C to 140°C for 5 hours. After the reaction, the toluene was evaporated, sodium hydroxide was added to make the mixture alkaline, and the precipitate was separated and finally washed with water, washed with alcohol, dried and set aside;
[0074] S2. Mixing cellulose diacetate and the epoxidized alkyl ester composition of the compound represented by Formula 1 in a high-speed mechanical stirrer for 2 minutes at room temperature, and then drying the mixture in a vacuum oven at 85° C. for 20 hours to obtain a plasticized mixture;
[0075] S3, adding the plasticized mixture into an ultrasonic twin-screw extruder, then adding an antioxidant into the ultrasonic twin-screw extruder, adding aromatic ether sulfone diamine during the melting process, and reacting at a temperature of 70° C. for 30 hours and an ultrasonic power of 1050 W to obtain cellulose diacetate grafted with aromatic ether sulfone diamine;
[0076] S4. Add maleic anhydride to an ultrasonic twin-screw extruder, add diacetate cellulose grafted with aromatic ether sulfone diamine (molar ratio 2.2:1) under stirring, react at 10°C to 25°C for 1 hour to obtain diacetate cellulose grafted with monomaleamic acid, then add p-toluenesulfonic acid and toluene, slowly heat up to 120°C, react for 4 hours to obtain diacetate cellulose grafted with aromatic ether sulfone monomaleimide, and after extrusion, cool to room temperature to produce particles to obtain a high-strength cellulose acetate material.
[0077] Example 3
[0078] This embodiment provides a high-strength cellulose acetate material, wherein the raw materials include, by mass percentage: 65% of cellulose diacetate grafted aryl ether sulfone monomaleimide, 33% of an epoxidized alkyl ester composition of a compound represented by Formula 1, and 2% of an antioxidant;
[0079] Formula 1
[0080]
[0081] Among them, the antioxidant can prevent the decomposition of cellulose diacetate caused by high temperature during the melting and heating process of the twin-screw extruder.
[0082] In this embodiment, the antioxidant is tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane.
[0083] R1 in Formula 1 is an alkyl group of 15 carbon atoms containing three epoxy groups; and R2 is selected from 2-ethylhexyl.
[0084] In this embodiment, the preparation method of cellulose diacetate grafted aryl ether sulfone monomaleimide comprises the following steps:
[0085] S1. Synthesis and purification of aromatic ether sulfone diamine: p-aminophenol, dichlorodiphenol, dimethyl sulfoxide, sodium hydroxide and toluene were added to a four-necked flask equipped with a stirrer, a water separator, a thermometer and a N2 tube, and the mixture was reacted at 120°C to 140°C for 5 hours. After the reaction, the toluene was evaporated, sodium hydroxide was added to make the mixture alkaline, the precipitate was separated, and the mixture was washed with water, alcohol and dried.
[0086] S2, cellulose diacetate grafted with aromatic ether sulfone diamine: adding aromatic ether sulfone diamine to a cellulose diacetate solution dissolved in cyclohexanone, reacting at 70°C for 30 hours, with an ultrasonic power of 1050W, and precipitating the reaction product in cold methanol, filtering, and washing with methanol to obtain cellulose diacetate grafted with aromatic ether sulfone diamine;
[0087] S3. Synthesis of cellulose diacetate grafted aryl ether sulfone monomaleimide (SEM):
[0088] In a three-necked flask equipped with a stirrer, a thermometer and a condenser, add maleic anhydride and dissolve it in dimethylformamide. Add diacetate cellulose grafted with aromatic ether sulfone diamine (molar ratio 2.2:1) under stirring, cool with cold water, react at 10°C to 25°C for 1h to obtain diacetate cellulose grafted with monomaleamic acid, then add p-toluenesulfonic acid and toluene, slowly heat to 120°C, react for 4h, cool to room temperature, pour into distilled water under stirring, filter out the brown viscous substance, rotary evaporate the filtrate, add dimethylformamide to dissolve it and precipitate it in water, filter, wash with alcohol, and dry to obtain diacetate cellulose grafted with aromatic ether sulfone monomaleimide.
[0089] This embodiment provides a method for preparing a high-strength cellulose acetate material, comprising the following steps:
[0090] S1. Synthesis and purification of aromatic ether sulfone diamine: p-aminophenol, dichlorodiphenol, dimethyl sulfoxide, sodium hydroxide and toluene were added to a four-necked flask equipped with a stirrer, a water separator, a thermometer and a N2 tube, and the mixture was reacted at 120°C to 140°C for 5 hours. After the reaction, the toluene was evaporated, sodium hydroxide was added to make the mixture alkaline, and the precipitate was separated and finally washed with water, washed with alcohol, dried and set aside;
[0091] S2. Mixing cellulose diacetate and the epoxidized alkyl ester composition of the compound represented by Formula 1 in a high-speed mechanical stirrer for 2 minutes at room temperature, and then drying the mixture in a vacuum oven at 90° C. for 30 hours to obtain a plasticized mixture;
[0092] S3, adding the plasticized mixture into an ultrasonic twin-screw extruder, then adding an antioxidant into the ultrasonic twin-screw extruder, adding aromatic ether sulfone diamine during the melting process, and reacting at a temperature of 70° C. for 30 hours and an ultrasonic power of 1050 W to obtain cellulose diacetate grafted with aromatic ether sulfone diamine;
[0093] S4. Add maleic anhydride to an ultrasonic twin-screw extruder, add diacetate cellulose grafted with aromatic ether sulfone diamine (molar ratio 2.2:1) under stirring, react at 10°C to 25°C for 1 hour to obtain diacetate cellulose grafted with monomaleamic acid, then add p-toluenesulfonic acid and toluene, slowly heat up to 120°C, react for 4 hours to obtain diacetate cellulose grafted with aromatic ether sulfone monomaleimide, and after extrusion, cool to room temperature to produce particles to obtain a high-strength cellulose acetate material.
[0094] Example 4
[0095] This embodiment provides a high-strength cellulose acetate material, wherein the raw materials include, by mass percentage: 75% of cellulose diacetate grafted aryl ether sulfone monomaleimide, 23% of an epoxidized alkyl ester composition of a compound represented by Formula 1, and 2% of an antioxidant;
[0096] Formula 1
[0097]
[0098] Among them, the antioxidant can prevent the decomposition of cellulose diacetate caused by high temperature during the melting and heating process of the twin-screw extruder.
[0099] In this embodiment, the antioxidant is tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane.
[0100] In Formula 1, R1 is an alkyl group having 10 carbon atoms and containing an epoxy group; and R2 is selected from an isononyl group.
[0101] In this embodiment, the preparation method of cellulose diacetate grafted aryl ether sulfone monomaleimide comprises the following steps:
[0102] S1. Synthesis and purification of aromatic ether sulfone diamine: p-aminophenol, dichlorodiphenol, dimethyl sulfoxide, sodium hydroxide and toluene were added to a four-necked flask equipped with a stirrer, a water separator, a thermometer and a N2 tube, and the mixture was reacted at 120°C to 140°C for 5 hours. After the reaction, the toluene was evaporated, sodium hydroxide was added to make the mixture alkaline, the precipitate was separated, and the mixture was washed with water, alcohol and dried.
[0103] S2, cellulose diacetate grafted with aromatic ether sulfone diamine: adding aromatic ether sulfone diamine to a cellulose diacetate solution dissolved in cyclohexanone, reacting at 70°C for 30 hours, with an ultrasonic power of 1050W, and precipitating the reaction product in cold methanol, filtering, and washing with methanol to obtain cellulose diacetate grafted with aromatic ether sulfone diamine;
[0104] S3. Synthesis of cellulose diacetate grafted aryl ether sulfone monomaleimide (SEM):
[0105] In a three-necked flask equipped with a stirrer, a thermometer and a condenser, add maleic anhydride and dissolve it in dimethylformamide. Add diacetate cellulose grafted with aromatic ether sulfone diamine (molar ratio 2.2:1) under stirring, cool with cold water, react at 10°C to 25°C for 1h to obtain diacetate cellulose grafted with monomaleamic acid, then add p-toluenesulfonic acid and toluene, slowly heat to 120°C, react for 4h, cool to room temperature, pour into distilled water under stirring, filter out the brown viscous substance, rotary evaporate the filtrate, add dimethylformamide to dissolve it and precipitate it in water, filter, wash with alcohol, and dry to obtain diacetate cellulose grafted with aromatic ether sulfone monomaleimide.
[0106] This embodiment provides a method for preparing a high-strength cellulose acetate material, comprising the following steps:
[0107] S1. Synthesis and purification of aromatic ether sulfone diamine: p-aminophenol, dichlorodiphenol, dimethyl sulfoxide, sodium hydroxide and toluene were added to a four-necked flask equipped with a stirrer, a water separator, a thermometer and a N2 tube, and the mixture was reacted at 120°C to 140°C for 5 hours. After the reaction, the toluene was evaporated, sodium hydroxide was added to make the mixture alkaline, and the precipitate was separated and finally washed with water, washed with alcohol, dried and set aside;
[0108] S2. At room temperature, cellulose diacetate and the epoxidized alkyl ester composition of the compound represented by Formula 1 were mixed in a high-speed mechanical stirrer for 2 minutes according to the formula amount, and then the mixture was dried in a vacuum oven at 70° C. for 24 hours to obtain a plasticized mixture;
[0109] S3, adding the plasticized mixture into an ultrasonic twin-screw extruder, then adding an antioxidant into the ultrasonic twin-screw extruder, adding aromatic ether sulfone diamine during the melting process, and reacting at a temperature of 70° C. for 30 hours and an ultrasonic power of 1050 W to obtain cellulose diacetate grafted with aromatic ether sulfone diamine;
[0110] S4. Add maleic anhydride to an ultrasonic twin-screw extruder, add diacetate cellulose grafted with aromatic ether sulfone diamine (molar ratio 2.2:1) under stirring, react at 10°C to 25°C for 1 hour to obtain diacetate cellulose grafted with monomaleamic acid, then add p-toluenesulfonic acid and toluene, slowly heat up to 120°C, react for 4 hours to obtain diacetate cellulose grafted with aromatic ether sulfone monomaleimide, and after extrusion, cool to room temperature to produce particles to obtain a high-strength cellulose acetate material.
[0111] Example 5
[0112] This embodiment provides a high-strength cellulose acetate material, the raw materials of which include, by mass percentage: 70% of cellulose diacetate grafted aryl ether sulfone monomaleimide, 28% of an epoxidized alkyl ester composition of a compound represented by Formula 1, 1% of an antioxidant, and 1% of a liquid crystal modifier;
[0113] Formula 1
[0114]
[0115] Among them, the antioxidant can prevent the decomposition of cellulose diacetate caused by high temperature during the melting and heating process of the twin-screw extruder.
[0116] In this embodiment, the antioxidant is tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane.
[0117] R1 in Formula 1 is an alkyl group of 18 carbon atoms containing two epoxy groups; and R2 is selected from 2-propylheptyl.
[0118] The preparation method of cellulose diacetate grafted aryl ether sulfone monomaleimide in this embodiment comprises the following steps:
[0119] S1. Add 2.0 g of cellulose diacetate into a strictly dried flask and purge it with dry nitrogen three times;
[0120] S2. Then, 6.69 g of p-dioxone (PDO) monomer was added to the strictly dried flask through a syringe, and the strictly dried flask was placed in a preheated oil bath at a temperature of 120° C. for 30 min to obtain a clear homogeneous solution system;
[0121] S3, then inject 0.84 mL of stannous octoate (Sn(Oct)2) solution under nitrogen conditions at 140°C, and react at a reaction temperature of 140°C for 2 hours;
[0122] S4. After rapidly cooling to 0°C, the crude product was dissolved in chloroform and precipitated with anhydrous methanol; the precipitate was then extracted with toluene and acetone for 48 hours for purification; and vacuum dried at 60°C to constant weight to obtain cellulose diacetate grafted aromatic ether sulfone monomaleimide.
[0123] This embodiment provides a method for preparing a high-strength cellulose acetate material, comprising the following steps:
[0124] S1. At room temperature, cellulose diacetate grafted aryl ether sulfone monomaleimide and the epoxidized alkyl ester composition of the compound represented by Formula 1 were mixed in a high-speed mechanical stirrer for 2 minutes according to the formula amount, and then the mixture was dried in a vacuum oven at 70° C. for 24 hours to obtain a plasticized mixture;
[0125] S2. Add the plasticized mixture into a twin-screw extruder, then add an antioxidant and a surfactant into the twin-screw extruder, and after melt extrusion, slice the cellulose diacetate grafted with aryl ether sulfone monomaleimide to produce a granular form to obtain a cellulose acetate material with high strength.
[0126] Furthermore, the preparation method of the liquid crystal modifier comprises the following steps:
[0127] S1, 4-(2-propyleneoxy)benzaldehyde: 4-hydroxybenzaldehyde (61.1 g, 0.5 mol), anhydrous K2CO3 (82.8 g, 0.6 mol) and dimethylformamide solution (250 mL) were added to a 500 mL three-necked round-bottom flask equipped with a mechanical stirrer and a reflux condenser, respectively, and stirred for 15 min; allyl bromide (72.6 g, 0.6 mol) dissolved in 50 mL of dimethylformamide solution was slowly added to a three-necked round-bottom flask equipped with a mechanical stirrer and a reflux condenser, and the slow addition time was 30 min. The mixture was refluxed under nitrogen for 24 h; the obtained solution was then poured into water, extracted three times with ether, and dried over anhydrous MgSO4. After the solvent was evaporated, a light yellow oil was obtained to obtain 4-(2-propyleneoxy)benzaldehyde;
[0128] S1. Dienyloxyazoimide: Aromatic diamine and 4-(2-propyleneoxy)benzaldehyde are mixed at a molar ratio of 1:2, the mixture is dissolved in dimethylformamide solution, a few drops of acetic acid are added, and the mixture is heated at 80°C for reaction. After the reaction is completed, the mixture is cooled to room temperature, and the obtained solution is poured into water. The solid is filtered out, washed with ethanol, and vacuum dried to obtain a liquid crystal modifier.
[0129] Example 6
[0130] This embodiment provides a high-strength cellulose acetate material, the raw materials of which include, by mass percentage: 69% of cellulose diacetate grafted aryl ether sulfone monomaleimide, 28% of an epoxidized alkyl ester composition of a compound represented by Formula 1, 1% of an antioxidant, and 2% of a liquid crystal modifier;
[0131] Formula 1
[0132]
[0133] Among them, the antioxidant can prevent the decomposition of cellulose diacetate caused by high temperature during the melting and heating process of the twin-screw extruder.
[0134] In this embodiment, the antioxidant is tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane.
[0135] R1 in Formula 1 is an alkyl group of 18 carbon atoms containing two epoxy groups; and R2 is selected from 2-propylheptyl.
[0136] The preparation method of cellulose diacetate grafted aryl ether sulfone monomaleimide in this embodiment comprises the following steps:
[0137] S1. Add 2.0 g of cellulose diacetate into a strictly dried flask and purge it with dry nitrogen three times;
[0138] S2. Then, 6.69 g of p-dioxone (PDO) monomer was added to the strictly dried flask through a syringe, and the strictly dried flask was placed in a preheated oil bath at a temperature of 120° C. for 30 min to obtain a clear homogeneous solution system;
[0139] S3, then inject 0.84 mL of stannous octoate (Sn(Oct)2) solution under nitrogen conditions at 140°C, and react at a reaction temperature of 140°C for 2 hours;
[0140] S4. After rapidly cooling to 0°C, the crude product was dissolved in chloroform and precipitated with anhydrous methanol; the precipitate was then extracted with toluene and acetone for 48 hours for purification; and vacuum dried at 60°C to constant weight to obtain cellulose diacetate grafted aromatic ether sulfone monomaleimide.
[0141] This embodiment provides a method for preparing a high-strength cellulose acetate material, comprising the following steps:
[0142] S1. At room temperature, cellulose diacetate grafted aryl ether sulfone monomaleimide and the epoxidized alkyl ester composition of the compound represented by Formula 1 were mixed in a high-speed mechanical stirrer for 2 minutes according to the formula amount, and then the mixture was dried in a vacuum oven at 70° C. for 24 hours to obtain a plasticized mixture;
[0143] S2. Add the plasticized mixture into a twin-screw extruder, then add an antioxidant and a surfactant into the twin-screw extruder, and after melt extrusion, slice the cellulose diacetate grafted with aryl ether sulfone monomaleimide to produce a granular form to obtain a cellulose acetate material with high strength.
[0144] Furthermore, the preparation method of the liquid crystal modifier comprises the following steps:
[0145] S1, 4-(2-propyleneoxy)benzaldehyde: 4-hydroxybenzaldehyde (61.1 g, 0.5 mol), anhydrous K2CO3 (82.8 g, 0.6 mol) and dimethylformamide solution (250 mL) were added to a 500 mL three-necked round-bottom flask equipped with a mechanical stirrer and a reflux condenser, respectively, and stirred for 15 min; allyl bromide (72.6 g, 0.6 mol) dissolved in 50 mL of dimethylformamide solution was slowly added to a three-necked round-bottom flask equipped with a mechanical stirrer and a reflux condenser, and the slow addition time was 30 min. The mixture was refluxed under nitrogen for 24 h; the obtained solution was then poured into water, extracted three times with ether, and dried over anhydrous MgSO4. After the solvent was evaporated, a light yellow oil was obtained to obtain 4-(2-propyleneoxy)benzaldehyde;
[0146] S1. Dienyloxyazoimide: Aromatic diamine and 4-(2-propyleneoxy)benzaldehyde are mixed at a molar ratio of 1:2, the mixture is dissolved in dimethylformamide solution, a few drops of acetic acid are added, and the mixture is heated at 80°C for reaction. After the reaction is completed, the mixture is cooled to room temperature, and the obtained solution is poured into water. The solid is filtered out, washed with ethanol, and vacuum dried to obtain a liquid crystal modifier.
[0147] Comparative Example
[0148] The difference from Example 1 is that the comparative example provides a cellulose acetate material, and the raw materials, calculated by mass percentage, include: 70% of diacetyl cellulose, 28% of the epoxidized alkyl ester composition of the compound represented by Formula 1, and 2% of an antioxidant.
[0149] Formula 1
[0150]
[0151] Among them, the antioxidant can prevent the decomposition of cellulose diacetate caused by high temperature during the melting and heating process of the twin-screw extruder.
[0152] The antioxidant in this comparative example is tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane, namely antioxidant 1010.
[0153] In Formula 1, R1 is an isononyl group having 8 carbon atoms and containing an epoxy group; and R2 is selected from a butyl group.
[0154] This comparative example provides a method for preparing a cellulose acetate material, comprising the following steps:
[0155] S1. At room temperature, cellulose diacetate and the epoxidized alkyl ester composition of the compound represented by Formula 1 were mixed in a high-speed mechanical stirrer for 2 minutes according to the formula amount, and then the mixture was dried in a vacuum oven at 70° C. for 24 hours to obtain a plasticized mixture;
[0156] S2. Add the plasticized mixture into a twin-screw extruder, then add an antioxidant into the twin-screw extruder, and after melt extrusion, slice the cellulose diacetate to produce a granular form to obtain a heat-resistant cellulose acetate material.
[0157] Experimental example
[0158] The cellulose acetate materials prepared in Examples 1-6 and the comparative example were prepared into samples of 18 mm×9 mm×1 mm.
[0159] The tensile strength was measured using an American instron universal material testing machine. The measurement results of the cellulose acetate materials prepared in Examples 1-6 and the comparative example are shown in Table 1.
[0160] The measurement of tensile strength reflects the energy required to break the film by stretching, and the value of Young's modulus reflects the ability of the sample to maintain its original shape after stress release. It is well known that the tensile strength of CA is about (15–60MPa) and the Young's modulus is about (600–3000MPa)
[0161] Dynamic Mechanical Thermal Analysis (DMTA) was performed under nitrogen conditions using a Rheo Solid Analyzer II (Rheometer Science Co., Ltd.). Dynamic Mechanical Thermal Analysis (DMTA) is a technique used to determine the mechanical properties of a material when subjected to a periodically changing mechanical load. DMTA can evaluate the viscoelastic properties of a material, including modulus (elastic modulus and loss modulus), damping properties, glass transition temperature (Tg), and other performance parameters related to temperature and frequency. The Young's modulus and glass transition temperature (Tg) of the cellulose acetate materials prepared in Examples 1-6 and Comparative Examples are shown in Table 1.
[0162] Examples 1-6 and the comparative example require at least 3 measurements on average, and the measurement results are shown in Table 1.
[0163] Table 1
[0164]
[0165] As can be seen from Table 1, the glass transition temperature (Tg), tensile strength, and Young's modulus of Examples 1-6 are significantly greater than those of the comparative example, which indicates that the diacetate cellulose grafted with aryl ether sulfone monomaleimide is a liquid crystal polymer, forming a highly cross-linked rigid rod network in the diacetate cellulose and liquid crystal phase, improving the rigidity of the molecular chain of diacetate cellulose, thereby improving the mechanical strength of the diacetate cellulose material. The glass transition temperature (Tg), tensile strength, and Young's modulus of Examples 5-6 are significantly greater than those of Examples 1-4, indicating that the liquid crystal modifier can increase the cross-linking degree of the liquid crystal polymer network, further improving the mechanical strength of the diacetate cellulose material.
[0166] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A high-strength cellulose acetate material, characterized in that: The raw materials include, by mass percentage: 65%-75% of cellulose diacetate grafted aryl ether sulfone monomaleimide, 23%-33% of an epoxidized alkyl ester composition of a compound represented by formula 1, and 1%-2% of an antioxidant; Formula 1 ; In Formula 1, R1 is an alkyl group of 8 to 20 carbon atoms containing one to three epoxy groups, and R2 is an alkyl group of 4, 5, or 8 to 10 carbon atoms; The cellulose diacetate grafted aryl ether sulfone monomaleimide is a liquid crystal polymer, wherein the aryl ether sulfone monomaleimide is a liquid crystal phase; the preparation method of the cellulose diacetate grafted aryl ether sulfone monomaleimide comprises the following steps: S1. Synthesis and purification of aromatic ether sulfone diamine: p-aminophenol, dichlorodiphenol, dimethyl sulfoxide, sodium hydroxide and toluene were added to a four-necked flask equipped with a stirrer, a water separator, a thermometer and a N2 tube, and the mixture was reacted at 120°C to 140°C for 5 hours. After the reaction, the toluene was evaporated, sodium hydroxide was added to make the mixture alkaline, the precipitate was separated, and the mixture was washed with water, washed with alcohol and dried. S2, cellulose diacetate grafted with aromatic ether sulfone diamine: adding the aromatic ether sulfone diamine to a cellulose diacetate solution dissolved in cyclohexanone, reacting at 70° C. for 30 h, with an ultrasonic power of 1050 W, precipitating the reaction product in cold methanol, filtering, and washing with methanol to obtain the cellulose diacetate grafted with aromatic ether sulfone diamine; S3. Synthesis of cellulose diacetate grafted aryl ether sulfone monomaleimide (SEM): In a three-necked flask equipped with a stirrer, a thermometer and a condenser, maleic anhydride is added and dissolved in dimethylformamide. The diacetate cellulose grafted with aromatic ether sulfone diamine is added under stirring, wherein the molar ratio of the maleic anhydride to the diacetate cellulose grafted with aromatic ether sulfone diamine is 2.2:
1. The mixture is cooled with cold water and reacted at 10°C to 25°C for 1 hour to obtain diacetate cellulose grafted with monomaleamic acid. P-toluenesulfonic acid and toluene are then added, the temperature is slowly raised to 120°C, the reaction is performed for 4 hours, the mixture is cooled to room temperature, the mixture is poured into distilled water under stirring, the brown viscous substance is filtered off, the filtrate is rotary evaporated, dimethylformamide is added to dissolve the filtrate and precipitate the filtrate in water, the filtrate is filtered, the filtrate is washed with alcohol and dried to obtain the diacetate cellulose grafted with aromatic ether sulfone monomaleimide.
2. A high-strength cellulose acetate material as claimed in claim 1, characterized in that: The raw materials, calculated by mass percentage, include: 70% of cellulose diacetate grafted aryl ether sulfone monomaleimide, 28% of the epoxidized alkyl ester composition of the compound represented by Formula 1, and 2% of an antioxidant.
3. A high-strength cellulose acetate material as claimed in claim 1, characterized in that: The antioxidant is tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane or tris(2,4-di-tert-butylphenyl)phosphite.
4. A high-strength cellulose acetate material as claimed in claim 1, characterized in that: R2 in Formula 1 is selected from the group consisting of butyl, pentyl, 2-ethylhexyl, isononyl and 2-propylheptyl.
5. A high-strength cellulose acetate material as claimed in claim 1, characterized in that: The raw materials, calculated by mass percentage, also include: 1%-2% of a liquid crystal modifier; the preparation method of the liquid crystal modifier comprises the following steps: S1, 4-(2-propyleneoxy)benzaldehyde: 4-hydroxybenzaldehyde, anhydrous K2CO3 and dimethylformamide solution were added to a 500 mL three-necked round-bottom flask equipped with a mechanical stirrer and a reflux condenser, respectively, and stirred for 15 min; the allyl bromide solution dissolved in 50 mL of dimethylformamide solution was slowly added to the three-necked round-bottom flask equipped with a mechanical stirrer and a reflux condenser, and the slow addition time was 30 min, and the mixture was refluxed under nitrogen for 24 h; then the obtained solution was poured into water, extracted with ether three times, and dried over anhydrous MgSO4. After the solvent was evaporated, a light yellow oil was obtained to obtain the 4-(2-propyleneoxy)benzaldehyde; S2. Dienyloxyazoimide: The aromatic diamine and the 4-(2-propyleneoxy)benzaldehyde are mixed at a molar ratio of 1:2, the mixture is dissolved in a dimethylformamide solution, a few drops of acetic acid are added, and the mixture is heated at 80°C to react. After the reaction is completed, the mixture is cooled to room temperature, and the obtained solution is poured into water, the solid is filtered out, washed with ethanol, and vacuum dried to obtain the liquid crystal modifier.
6. A method for preparing a high-strength cellulose acetate material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Synthesis and purification of aromatic ether sulfone diamine: add p-aminophenol, dichlorodiphenol, dimethyl sulfoxide, sodium hydroxide and toluene to a four-necked flask equipped with a stirrer, a water separator, a thermometer and a N2 tube, and react at 120°C-140°C for 5 hours. After the reaction, evaporate the toluene, add sodium hydroxide to make it alkaline, separate the precipitate, wash with water, wash with alcohol, dry and set aside; S2. At room temperature, cellulose diacetate and the epoxidized alkyl ester composition of the compound represented by Formula 1 are mixed in a high-speed mechanical stirrer for 2 minutes according to the formula amount, and then the mixture is dried in a vacuum oven at 70° C. to 90° C. for 20 to 30 hours to obtain a plasticized mixture; S3, adding the plasticized mixture into an ultrasonic twin-screw extruder, then adding the antioxidant into the ultrasonic twin-screw extruder, adding the aromatic ether sulfone diamine during the melting process, reacting at a temperature of 70° C. for 30 hours and an ultrasonic power of 1050 W to obtain the cellulose diacetate grafted aromatic ether sulfone diamine; S4. Add the maleic anhydride into the ultrasonic twin-screw extruder, add the cellulose diacetate grafted aromatic ether sulfone diamine under stirring, react at 10° C. to 25° C. for 1 hour to obtain cellulose diacetate grafted monomaleamic acid, then add p-toluenesulfonic acid and toluene, slowly heat up to 120° C., react for 4 hours to obtain the cellulose diacetate grafted aromatic ether sulfone monomaleimide, and after extrusion, cool to room temperature to produce particles to obtain the cellulose acetate material with high strength.
7. The method for preparing a high-strength cellulose acetate material according to claim 6, characterized in that: In step S2, the mixture is dried in a vacuum oven at 70°C for 24 hours.
8. Use of a high-strength cellulose acetate material according to any one of claims 1 to 5, characterized in that: The high-strength cellulose acetate material is used to manufacture eyeglass frames and high-grade tool handles.
Citation Information
Patent Citations
Cellulose derivative, thermoformed material, molded body, production method therefor, and casing for electrical and electronic equipment
CN102471539A
Preparation method of cellulose diacetate particles
CN104558640A